Protagonisms of Dissident Corporealities:: creative processes for the project Decolonizando Práticas Cênicas... - Colin, Daniel dos Santos (Revista Brasileira de Estudos da Presença, 2024)
Protagonisms of Dissident Corporealities: creative processes for the project Decolonizando Práticas Cênicas... – This text presents fundamental principles of the decolonial perspective in possible intersections with the arts of the body. A brief critical reflection is made on the artistic-pedagogical activities that made up the cultural project Decolonizando Práticas Cênicas… (Decolonizing Scenic Practices…), held in 2021, which central objective was to praise dissident subjects and their effective elevation to the status of protagonists of authorial videoperformances. Some of these works are analyzed using concepts and practices that permeate the performing arts, the decolonial turn and gender and sexuality studies.